1998
DOI: 10.2331/fishsci.64.329
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Factor Stimulating Salinity Tolerance and Branchial Chloride Cells in a Euryhaline Teleost <i>Poecilia reticulata</i>

Abstract: The present study examined a factor in seawater which stimulates salinity tolerance and the num ber and size of branchial chloride cells in the guppy. Salinity tolerance was measured as LD50 24 h after transfer to serial concentrations of salinity. LD50 significantly increased from 25.8 ppt to 43.3 ppt 5 days after exposure to 15 ppt dilute seawater. Thus, increases of salinity tolerance were examined on the basis of 5 days' exposure to various solutions which were contained within 15 ppt dilute seawater. LD50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Several investigators have demonstrated the wide salinity tolerance of poeciliid fishes such as P. reticulata (cf. Arai et al 1998), Limia melanonotata (cf. Haney and Walsh 2003), P. sphenops (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have demonstrated the wide salinity tolerance of poeciliid fishes such as P. reticulata (cf. Arai et al 1998), Limia melanonotata (cf. Haney and Walsh 2003), P. sphenops (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is a major influencing factor on reproductive physiology in fishes (Ellis et al, 1997;Watanabe et al, 1998;Claireaux and Lagardere, 1999). Although several investigators reported salinity tolerance of poeciliid fishes (Kristensen, 1969;Nordlie et al, 1992;Arai et al, 1998), no scientific work on the effect of salinity on breeding and growth performance of P. latipinna has been done. The goal of the present study was to assess the effect of salinity on breeding and growth performance of P. latipinna in captive conditions.…”
Section: Introductionmentioning
confidence: 99%